2021
DOI: 10.1038/s41523-020-00212-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of systemic inflammation on relapse in early breast cancer

Abstract: Chronic inflammation has been a proposed mechanism of resistance to aromatase inhibitors in breast cancer. Stratifying by HER2 status, a matched case-control study from the Wellness After Breast Cancer-II cohort was performed to assess whether or not elevated serum inflammatory biomarkers (C-Reactive protein [CRP], interleukin-6 [IL-6], and serum amyloid A [SAA]) and/or the presence of a high-risk IL-6 promoter genotype were associated with recurrence of hormone receptor positive (HR+) early breast cancer. Est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 37 publications
(47 reference statements)
0
24
0
Order By: Relevance
“…Interestingly, several studies have demonstrated an increase in inflammatory infiltrates in the subtype hormone receptor-negative breast cancer, including high lymphocytic infiltrate, plasma cell infiltrate, other inflammatory cell infiltrate and macrophage infiltrate associated with ER neg/PR neg tumors [84], higher numbers of peri-and paratumoral tumor infiltrating B lymphocytes associated significantly with hormone receptor (ER/PR) negative (p = 0.008) and HER2+ status [119], and high granulin expressing bone marrow cells recruited to breast cancer expression and correlated with the most aggressive triplenegative, basal-like tumor subtype [120]. On the other hand, serum CRP, a marker of chronic inflammation, appears to be independent of tumor subtype, with elevations in receptor-positive as well as receptor-negative tumors [121][122][123][124].…”
Section: Chronic Inflammatory Cell Infiltrates In Breast Cancer Tissuesmentioning
confidence: 99%
“…Interestingly, several studies have demonstrated an increase in inflammatory infiltrates in the subtype hormone receptor-negative breast cancer, including high lymphocytic infiltrate, plasma cell infiltrate, other inflammatory cell infiltrate and macrophage infiltrate associated with ER neg/PR neg tumors [84], higher numbers of peri-and paratumoral tumor infiltrating B lymphocytes associated significantly with hormone receptor (ER/PR) negative (p = 0.008) and HER2+ status [119], and high granulin expressing bone marrow cells recruited to breast cancer expression and correlated with the most aggressive triplenegative, basal-like tumor subtype [120]. On the other hand, serum CRP, a marker of chronic inflammation, appears to be independent of tumor subtype, with elevations in receptor-positive as well as receptor-negative tumors [121][122][123][124].…”
Section: Chronic Inflammatory Cell Infiltrates In Breast Cancer Tissuesmentioning
confidence: 99%
“…Interleukin-6 IL-6 is a B-cell differentiation factor and Th2-related factor, secreted mainly by mast cells and T cells, involved in inflammation, hematopoiesis, immune regulation, and other functions. According to the reports, IL-6 participates in many diseases including autoimmune diseases, mastocytosis, and even breast cancer [37,38]. IL-6 is increased in urticaria, which is related to the activity of the disease, and patients with elevated serum IL-6 levels are not ideal for antihistamines, which indicates that IL-6 promotes mast cell proliferation and activation.…”
Section: Il-6/janus Tyrosine Kinase/stat Pathwaymentioning
confidence: 99%
“…Curtis TCGA data mining inversely correlated expression levels of oncostatin M (OSM), IL-6, and IL-1β with breast cancer patient survival [ 107 ]. Elevated serum inflammatory biomarkers including C-reactive protein (CRP), IL-6, and serum amyloid A (SAA) were positively associated with an increased risk of recurrence of HR+/HER2- tumor, and higher CRP level was correlated with detectable serum estrogen metabolites [ 108 ]. Intriguingly, IL-6 was positively correlated with prognostic factors in both ER+ and ER– patients [ 109 ].…”
Section: Estrogen Inflammation and Breast Cancermentioning
confidence: 99%